MAP ZONE LAND CHANGES TO MONITORING OF CHANGE THE VALUE OF LAND AT DISTRICT RUNGKUT - Deviantari , Udiana Wahyu; Budisusanto, Yanto; Arafah, Feni (Departemen Teknik Geomatika ITS, 2016)
The rising of land value is closely related to development process. Middle East Ring Road (MERR) development results in the rapid growth of settlement and other business activities around it. Based on RTRW Surabaya no. 3/2007 about Main Road Network Plan,It wasstated that the land use along MERR II-C will be allocated for trading, service, and public facilities. With so many activities at the site, thelimited land will be fought among users in order to gain maximum benefit. The rapid change in the value / market price of land in the region led to users struggling in keeping updates of land value.Determining the land value or land marketcan be obtained by using Land Value Zone (ZNT) map. ZNT map illustrates areas that has arelatively similar land value. Land value data used in this study is the land market in 2010-2014. The production of land value mapwas by using spatial analysis techniques to create zones or polygon-shaped area that represents the land value in accordance with the real conditions in the field on buying or selling value.ZNT processing results in 6 Village in Rungkut District show a change in the land value; the highest is located in the zone AC and AH in Kalirungkut sub district, while the least changes is in zone FH in Rungkut Kidul sub district. Changes in land value occursin Kalirungkut sub district because of population density and high social activities.While the change in the land value in the Rungkut Kidul sub district is due to the development of education activity, availability of education facility (UPN campus) and accessibility to MERR.